An Assessment into Physical and Proximate Analysis of Processed Locust Bean (Parkia biglobosa) Preserved with Common Salt - Ademola, I.T.; Baiyewu, R.A.; Adekunle, E.A.; Omidiran, M.B.; Adebawo, F.G. (Pakistan Journal of Nutrition, 2011)
This study was aimed at assessing the effect of salt on the nutritive value and proximate composition of processed Locust bean seeds (Parkia biglobosa) which were preserved with salt. In this work, salted and unsalted processed locust bean were subjected to organoleptic and proximate analyses at one week interval of for four consecutive weeks. There was 7.98% reduction in the moisture content of the salted samples after 4 weeks (against 4.86% increase in the unsalted). This shows that salting decreased the moisture content, thus discouraging microbial growth and food spoilage. The carbohydrate content of the salted and unsalted samples decreased alike by 51.51%. The results obtained showed that the salting is a good method of preserving locust bean; as the method retained its physical characteristics.